Evaluation of a non-radioactive rapid test for the determination of serum progesterone in the mare - Längerer, Lina; Schuler, Gerhard; Büttner, Kathrin; Wehrend, Axel; Justus Liebig University Giessen (My University, 2025)
The determination of progesterone from mares’ serum plays a decisive role in diagnosing estrus cycle disorders or luteal insufficiency. To date, no measurement methods are available for rapid quantitative diagnosis of serum progesterone in the mare that would allow results to be available within a two-hour time frame. The present study will evaluate a commercial enzyme-linked fluorescent assay, the mini VIDAS device (bioMérieux, Nürtingen, Germany). Serum was prepared from the blood samples of one hundred and seven mares, divided into two aliquots, and stored at –20°C. Subsequently, comparative progesterone measurements were carried out using radioimmunoassay (RIA) and mini VIDAS, with RIA as the reference standard. The results show a strong positive correlation between the two measurement methods (Spearman rank correlation rs = 0.96381 (p < 0.05). The tests confirm that the mini VIDAS can be used for equine serum progesterone concentration determination and provides reliable results in less than an hour. For accurate estrus cycle diagnostics, high precision in the low measurement range is essential, as even minor deviations can result in ovulation misdiagnosis. Despite the high correlation of the measuring methods, deviations from the reference method can be observed in the low measuring range of the mini VIDAS, which suggests potential limitations of this study.
Keywords: ddc:630